Multi‐omics profiling of a CHO cell culture system unravels the effect of culture pH on cell growth, antibody titer, and product quality. Issue 11 (31st July 2021) - Lee, Alison P.; Kok, Yee Jiun; Lakshmanan, Meiyappan; Leong, Dawn; Zheng, Lu; Lim, Hsueh Lee; Chen, Shuwen; Mak, Shi Ya; Ang, Kok Siong; Templeton, Neil; Salim, Taha; Wei, Xiaona; et al.
Abstract: A robust monoclonal antibody (mAb) bioprocess requires physiological parameters such as temperature, pH, or dissolved oxygen to be well‐controlled as even small variations in them could potentially impact the final product quality. For instance, pH substantially affects N‐glycosylation, protein aggregation, and charge variant profiles, as well as mAb productivity. However, relatively less is known about how pH jointly influences product quality and titer. In this study, we investigated the effect of pH on culture performance, product titer, and quality profiles by applying longitudinal multi‐omics profiling, including transcriptomics, proteomics, metabolomics, and glycomics, at three different culture pH set points. The subsequent systematic analysis of multi‐omics data showed that pH set points differentially regulated various intracellular pathways including intracellular vesicular trafficking, cell cycle, and apoptosis, thereby resulting in differences in specific productivity, product titer, and quality profiles. In addition, a time‐dependent variation in mAb N‐glycosylation profiles, independent of pH, was identified to be mainly due to the accumulation of mAb proteins in the endoplasmic reticulum disrupting cellular homeostasis over culture time. Overall, this multi‐omics‐based study provides an in‐depth understanding of the intracellular processes in mAb‐producing CHO cell line under varied pH conditions, and could serve as a baseline for enabling the quality optimization and control of mAb production. Abstract : A multi‐omics based approach was employed to investigate how pH variations affect mAb titer and quality attributes in CHO cell cultures. pH variations were found to differentially regulate various CHO intracellular processes, including intracellular vesicular trafficking, cell cycle and apoptosis, thus influencing the product titer and quality profiles. The insights gained from this study are expected to significantly contribute towards the development of targeted approaches for effective mAb quality control during biomanufacturing.